Efficacy, tolerability and management of raltitrexed (Tomudex) monotherapy in patients with advanced colorectal cancer. a review of phase II/III trials. - Cunningham, D; Zalcberg, J; Maroun, J; James, R; Clarke, S; Maughan, T; Vincent, M; Schulz, J; González Barón, M; Facchini, T (2002)
Raltitrexed (Tomudex), a thymidylate synthase inhibitor, is an alternative to 5-fluorouracil (5-FU)/leucovorin (LV) for the first-line treatment of advanced colorectal cancer. Following the completion of four phase III studies with raltitrexed at the recommended dose of 3.0 mg/m(2), it is opportune to review the efficacy and tolerability data of raltitrexed and suggest guidelines for appropriate patient management. Data are analysed from four phase III and five phase II studies including over 1300 patients with advanced colorectal cancer, some of whom were elderly or received higher doses of raltitrexed. Median survival with raltitrexed was comparable to that of bolus or infusional 5-FU/LV in three of the four randomised studies and objective response rates in the four trials were similar for the two agents. Response rates were at least comparable in elderly patients in phase II studies. For the majority of patients, treatment with raltitrexed was well tolerated even at doses higher than that recommended or in the elderly. As with other cytotoxic agents, serious and potentially life-threatening side-effects can occur; nevertheless, adherence to simple patient guidelines should minimise the incidence of serious side-effects with raltitrexed; these include the assessment of renal function before each and every treatment, dosage adjustment in the presence of renal impairment and close monitoring with prompt treatment of toxicities, particularly diarrhoea and neutropenia.